Совершенствование законодательства, регулирующего внедоговорную ответственность - Сосна, Александр (Tipografia "CentroGrafic" ,Cahul, 2015)
At research of the questions, related to perfection of legislation regulative noncontractual responsibility, an author pays attention to their large theoretical and practical value. Some contradictions and defects are educed in a current legislation. And most notable is that additions and changes are offered in law enforcement.